Multivalent S2 subunit vaccines provide broad protection against Clade 1 sarbecoviruses in female mice - Halfmann, Peter J.; Patel, Raj S.; Loeffler, Kathryn; Yasuhara, Atsuhiro; Van De Velde, Lee-Ann; Yang, Jie E.; Chervin, Jordan; Troxell, Chloe; Huang, Min; Zheng, Naiying; Wright, Elizabeth R.; Thomas, Paul G.; et al. (Nature communications, 2025)
The continuing emergence of immune evasive SARS-CoV-2 variants and the previous SARS-CoV-1 outbreak collectively underscore the need for broadly protective sarbecovirus vaccines. Targeting the conserved S2 subunit of SARS-CoV-2 is a particularly promising approach to elicit broad protection. Here, we describe a nanoparticle vaccine displaying multiple copies of the SARS-CoV-1 S2 subunit. This vaccine alone, or as a cocktail with a SARS-CoV-2 S2 subunit vaccine, protects female transgenic K18-hACE2 mice from challenges with Omicron subvariant XBB as well as several sarbecoviruses identified as having pandemic potential including the bat sarbecovirus WIV1, BANAL-236, and a pangolin sarbecovirus. Challenge studies in female Fc-γ receptor knockout mice reveal that antibody-based cellular effector mechanisms play a role in protection elicited by these vaccines. These results demonstrate that our S2-based vaccines provide broad protection against clade 1 sarbecoviruses and offer insight into the mechanistic basis for protection. Understanding the induced and cross reactive immunity to sarbecoviruses is an important step in rationale and widely applicable vaccine design. Here the authors use a multivalent S2 subunit vaccine and demonstrate protection in female mice against SARS-CoV-2-like and SARS-CoV-1-like coronaviruses.